TREN KEPENULISAN PUBLIKASI PENELITIAN INDONESIA PADA JURNAL SCOPUS - Ibrahim, Cecep (Journal of Documentation and Information Science, 2019)
This study discusses the trend of authorship publication research indonesia indexed journal Scopus. The focus of this research is divided into four parts, namely the institution of a productive institutions, or the distribution of the subject of the research results, productive author, and the percentage of the productive author indexed journal Scopus. This research method using a Sistematik Literature Review approach to the consisted of three stages, namely planning the review (problem identification), conducting the review (the collection, selection and synthesis of data) and reporting the results of the analysis (review the discussion). The results of this research is divided into four parts based on index Scopus. First, the institution or institutions productive is the Bandung Institute of technology as much as document 10029. Second, the distribution of the subject of the research is the largest Engineering. Third, the productive author was Munir, A. as much as 217 documents. Fourth, the percentage of the author's productive is in the Education category, University/Institute of 77%).